A new human challenge model for testing heat-stable toxin-based vaccine candidates for enterotoxigenic Escherichia coli diarrhea - dose optimization, clinical outcomes, and CD4+T cell responses - Sakkestad S.T.; Steinsland H.; Skrede S.; Lillebo K.; Skutlaberg D.H.; Guttormsen A.B.; Zavialov A.; Paavilainen S.; Soyland H.; Saevik M.; Heien A.R.; Tellevik M.G.; et al. (PUBLIC LIBRARY SCIENCE, 2022)
Enterotoxigenic Escherichia coli (ETEC) are a common cause of diarrheal illness in young children and travelers. There is yet no licensed broadly protective vaccine against ETEC. One promising vaccine development strategy is to target strains expressing the heat-stable toxin (ST), particularly the human ST (STh), since infections with these strains are among the leading causes of diarrhea in children in low-and-middle income countries. A human challenge model based on an STh-only ETEC strain will be useful to evaluate the protective efficacy of new ST-based vaccine candidates. To develop this model, we experimentally infected 21 healthy adult volunteers with the epidemiologically relevant STh-only ETEC strain TW10722, identified a suitable dose, assessed safety, and characterized clinical outcomes and immune responses caused by the infection. Doses of 1x10(10) colony-forming units (CFU) of TW10722 gave a suitable attack risk of 67% for moderate or severe diarrhea and an overall diarrhea attack risk of 78%. Non-diarrheal symptoms were mostly mild or moderate, and there were no serious adverse events. During the first month after ingesting the challenge strain, we measured significant increases in both activated CD4+ T cells and levels of serum IgG and IgA antibodies targeting coli surface antigen 5 (CS5) and 6 (CS6), as well as the E. coli mucinase YghJ. The CS5-specific CD4+ T cell and antibody responses were still significantly elevated one year after experimental infection. In conclusion, we have developed a safe STh-only ETEC-based human challenge model which can be efficiently used in Phase 2B trials to evaluate the protective efficacy of new ST-based vaccine candidates.